2014
DOI: 10.1186/1746-6148-10-75
|View full text |Cite
|
Sign up to set email alerts
|

High-dose dietary zinc oxide mitigates infection with transmissible gastroenteritis virus in piglets

Abstract: BackgroundZinc (Zn) supplementation has been shown to reduce the incidence of diarrhea and to protect animals from intestinal diseases, but the mechanisms of this protective effect against virus infection in vivo have not yet been elucidated. Transmissible gastroenteritis virus (TGEV) causes diarrhea in piglets with an age-dependent decrease of severity.ResultsWe used 60 weaned piglets that were divided into three groups to evaluate the effect of different Zn levels added to a conventional diet (50 mg Zn/kg di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…Indeed, Slc30a1 and Wdr45 were respectively increased following exposure to ZnO and ZnFe 2 O 4 NPs. Noteworthy is the upregulation of Zn transporter Slc30a1after exposure to Zn element which has already been observed following an in vivo exposure of Zn to piglets (Chai et al 2014). Moreover, the higher amount of Zn element found in cells exposed to ZnO NPs, in addition to their soluble potential, could be related to the transient expression of Zn-dependent proteins, such as those encoded by Slc30a genes, Zfand2b, Zgpat, Zfp637, or Zfyve19 (Table S1a and S1b).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, Slc30a1 and Wdr45 were respectively increased following exposure to ZnO and ZnFe 2 O 4 NPs. Noteworthy is the upregulation of Zn transporter Slc30a1after exposure to Zn element which has already been observed following an in vivo exposure of Zn to piglets (Chai et al 2014). Moreover, the higher amount of Zn element found in cells exposed to ZnO NPs, in addition to their soluble potential, could be related to the transient expression of Zn-dependent proteins, such as those encoded by Slc30a genes, Zfand2b, Zgpat, Zfp637, or Zfyve19 (Table S1a and S1b).…”
Section: Discussionmentioning
confidence: 89%
“…Our results are in agreement with those of Tuomela et al (2013) who demonstrated an overexpression of different metallothioneins as a gene signature of three different immune cell lines after the exposure to ZnO NPs. Other recent studies revealed as well the expression of MTs after exposure to Zn, nano-ZnO, or micro-ZnO (Chai et al 2014;Safar et al 2018;Yang et al 2017). The overexpression of metallothioneins is an indicator of an adaptive response that plays a role in defense mechanisms against oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…ZO-1 zonula occludens-1, IL-1β interleukin-lβ, TNF-α tumor necrosis factor-α, IFN-γ interferon-γ, TGF-β transforming growth factor-β a, b Means within a row without a common superscript are significantly different (P < 0.05) Values are mean ± SEM, n = 4 gastroenteritis virus in piglets [14]. The alleviation of diarrhea, on the other hand, will enhance the normal growth of neonate children and piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also suggested that probiotics supplementation modified the gut microbiota by inducing an increase in lactobacilli and a decrease in E. coli (Hayakawa et al., ). Peptide‐zinc complexes in the probiotic compound used in this study also likely contributed to enhance the immune system of sows, as addition of zinc‐oxide to feed was previously shown to help reduce diarrhea incidence and assist in weight gain in pigs (Chai et al., ). Thus, a supply of beneficial bacterial strains and zinc to PED‐infected sows likely enhanced their overall health, which permitted them to eat more, better utilizing nutrients from feed, and gaining more weight.…”
Section: Discussionmentioning
confidence: 98%